2022
DOI: 10.21037/ccts-20-115
|View full text |Cite
|
Sign up to set email alerts
|

Stage IIIA non-small cell lung cancer: a contraindication for video-assisted thoracic surgery lobectomy?—a narrative review

Abstract: Answering the question about contraindications for video-assisted thoracic surgery (VATS) in stage IIIA non-small cell lung cancer (NSCLC) is not simple, as stage IIIA relates to a heterogeneous group of bronchogenic carcinomas with locoregional involvement by extension of the primary tumor as well as ipsilateral nodal involvement posing a significant challenge in terms of surgical indication. VATS is imposing over open surgery as the standard of surgical care for early stage lung cancer, showing benefits i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…11,12,18 Minor chest wall resections, especially in lung cancer surgery, are no longer strict contraindications for minimally invasive approaches and can be carried out through video-assisted thoracic surgery (VATS) or robot-assisted thoracic surgery (RATS) in selected cases. [19][20][21][22][23] In the end, the feasibility and practicability of the planned approach as well as extent of resection and reconstruction can only be finally determined intraoperatively, but the best possible preoperative planning will surely lead to better reliability in terms of resources, reconstruction methods and materials, and a beneficial outcome for the patient.…”
Section: Central Messagementioning
confidence: 99%
“…11,12,18 Minor chest wall resections, especially in lung cancer surgery, are no longer strict contraindications for minimally invasive approaches and can be carried out through video-assisted thoracic surgery (VATS) or robot-assisted thoracic surgery (RATS) in selected cases. [19][20][21][22][23] In the end, the feasibility and practicability of the planned approach as well as extent of resection and reconstruction can only be finally determined intraoperatively, but the best possible preoperative planning will surely lead to better reliability in terms of resources, reconstruction methods and materials, and a beneficial outcome for the patient.…”
Section: Central Messagementioning
confidence: 99%
“… 3 VATS is progressively replacing open surgery as the standard of surgical therapy for early-stage lung cancer, demonstrating improvements in postoperative pain, morbidity, recovery and lung function preservation. 4 In comparison with the conventional multiportal approach, studies have shown that UVATS is a safe and feasible technique for advanced stages of nonsmall-cell lung cancer. 5 However, with the advancement of technology and surgical skills, UVATS has become a challenging option for treating T4 lung tumours, even though published data remain limited.…”
Section: Introductionmentioning
confidence: 99%